Moxibustion for treating cancer‐related fatigue: A multicenter, assessor‐blinded, randomized controlled clinical trial - Han, Kyungsun (Cancer Med, 2021)
Cancer‐related fatigue (CRF) is one of the most common chronic symptoms experienced by cancer patients. As moxibustion is a popular traditional therapy for managing fatigue, it can be an alternative strategy to treat CRF as well. Therefore, we rigorously designed a full‐scale, multicenter, assessor‐blinded, randomized controlled trial to evaluate the efficacy and safety of moxibustion treatment for CRF. Ninety‐six subjects suffering from CRF were recruited and randomly assigned to moxibustion group, sham moxibustion group, or usual care group. Both the moxibustion group and the sham group received moxibustion treatment for 8 weeks and the usual care group did not. Brief fatigue inventory (BFI) score and Functional Assessment of Cancer Therapy‐Fatigue score were used to assess CRF at baseline and weeks 5, 9, and 13. Questionnaires for the assessment of cognitive impairment, quality of life, and Cold–Heat and Deficiency–Excess patterns were also evaluated. BFI scores significantly decreased in moxibustion group compared to the usual care group (mean difference of −1.92, p < 0.001 at week 9 and mean difference of −2.36, p < 0.001 at week 13). Although the sham group also showed significant improvement during the treatment period, only the moxibustion group showed improvement after 4 weeks of follow‐up period (mean difference of −1.06, p < 0.001). There were no serious adverse events. Our findings confirmed the efficacy and safety of moxibustion for CRF compared to usual care. We also found that moxibustion has a prolonged treatment effect during 4 weeks of follow‐up period.